PENERAPAN PENDEKATAN PEMBELAJARAN BERDIFERENSIASI UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF PADA MATA PELAJARAN IPAS KELAS V DI SD NEGERI LANGUNG - Dessi Noviati; Dian Kristanti; Mulyadi (Jurnal Binagogik, 2026)
This study aims to describe the application of a differentiated learning approach that can improve creative thinking skills and to describe students' creative thinking skills in the application of a differentiated learning approach to the subject of Science for Grade V at SD Negeri Langung. The type of research used is classroom action research. The subjects taken in this study were all students of grade V of SD Negeri Langung, with a total of 18 students. Data collection techniques used in this study were observation, tests, questionnaires and documentation. The instruments used to collect data in this study consisted of observation sheets, test sheets, questionnaire sheets and validation sheets. The conclusion of this study is that the application of a differentiated learning model in the subject of Science for Grade V at SD Negeri Langung, Meureubo District, namely teachers design learning based on three main differentiations, namely content differentiation, process differentiation and product differentiation, preparation of teaching modules, adjustment of media or methods used for each group, and fair assessment and according to the needs of each student. Differentiated learning is implemented, and teachers conduct assessments and reflections. The differentiated learning model can improve students' creative thinking skills. This is evident in the percentage of 18 students completing the pre-cycle, with 5 (27.78%) completing the task. In the first cycle, 8 (44.44%) completed the task. Furthermore, the second cycle showed a significant increase in students' creative thinking skills, with 16 students completing the task (88.89%) and only 2 students failing to complete the task (11.11%).